2020
DOI: 10.3390/jcm9113533
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Inflammatory Bowel Disease Are Not at Increased Risk of COVID-19: A Large Multinational Cohort Study

Abstract: The impact of COVID-19 on inflammatory bowel disease (IBD) patients under pharmacological immunosuppression is still not clearly understood. We investigated the incidence of COVID-19 and the impact of immunosuppression and containment measures on the risk of SARS-CoV-2 infection in a large IBD cohort, from a multicenter cohort from 21st of February to 30th of June, 2020. Ninety-seven patients with IBD (43 UC, 53 CD, one unclassified IBD) and concomitant COVID-19 over a total of 23,879 patients with IBD were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 15 publications
5
43
1
5
Order By: Relevance
“…A large multicentric Western collaborative study reported a cumulative incidence of SARS‐CoV‐2 infection in patients with IBD of 0.4% (97 out of 23879), comparable to that of the general population (0.4%), 93 thus excluding an increased or reduced risk of COVID‐19 for these patients. The authors 93 also found that corticosteroids increased the risk of hospitalization [odds ratio (OR) 7.6], whereas monoclonal antibodies therapy reduced the risk of pneumonia and hospitalization (OR 0.1 and 0.3, respectively). Taken together, these data suggest that the risk of SARS‐CoV‐2 infection of patients with IBD seems comparable to that of the general population.…”
Section: Clinical Featuresmentioning
confidence: 90%
See 2 more Smart Citations
“…A large multicentric Western collaborative study reported a cumulative incidence of SARS‐CoV‐2 infection in patients with IBD of 0.4% (97 out of 23879), comparable to that of the general population (0.4%), 93 thus excluding an increased or reduced risk of COVID‐19 for these patients. The authors 93 also found that corticosteroids increased the risk of hospitalization [odds ratio (OR) 7.6], whereas monoclonal antibodies therapy reduced the risk of pneumonia and hospitalization (OR 0.1 and 0.3, respectively). Taken together, these data suggest that the risk of SARS‐CoV‐2 infection of patients with IBD seems comparable to that of the general population.…”
Section: Clinical Featuresmentioning
confidence: 90%
“…91,92 A large multicentric Western collaborative study reported a cumulative incidence of SARS-CoV-2 infection in patients with IBD of 0.4% (97 out of 23879), comparable to that of the general population (0.4%), 93 thus excluding an increased or reduced risk of COVID-19 for these patients. The authors 93 also found that corticosteroids increased the risk of hospitalization [odds ratio (OR) 7.6],…”
Section: Inflammatory Bowel Diseasementioning
confidence: 98%
See 1 more Smart Citation
“…The Coronavirus Disease 19 (COVID-19) is a systemic infection caused by the new Severe Acute Respiratory Syndrome-Coronavirus 2 (SARS-CoV-2), which has impacted on Health Systems, and has led to a dramatic shrinkage of the world economy [ 1 ]. The risk of COVID-19 in patients with inflammatory bowel disease (IBD) is similar to the general population [ 1 3 ]. In a large cohort, the cumulative incidence of SARS-CoV-2 infection in patients with IBD versus the general population was 0.406% and 0.402% cases, respectively [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of COVID-19 in patients with inflammatory bowel disease (IBD) is similar to the general population [ 1 3 ]. In a large cohort, the cumulative incidence of SARS-CoV-2 infection in patients with IBD versus the general population was 0.406% and 0.402% cases, respectively [ 1 ]. Advances in age and treatment with corticosteroids impacted negatively on the outcome of COVID-19 [ 1 ].…”
Section: Introductionmentioning
confidence: 99%